Marine systems identification, modeling and control - Roskilly, Tony; Mikalsen, Rikard (Butterworth-Heinemann, 2015)
Marine Systems Identification, Modeling and Control is a concise, stand-alone resource covering the theory and practice of dynamic systems and control for marine engineering students and professionals. Developed from a distance learning CPD course on marine control taught by the authors, the book presents the essentials of the subject, including system representation and transfer, feedback control and closed loop stability. Simulation code and worked examples are provided for both Scilab and MATLAB, making it suitable for both those without access to expensive software and those using MATLAB in a professional setting. This title considers the key topics without superfluous detail and is illustrated with marine industry examples.